2019
DOI: 10.21307/sjcapp-2019-008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in delinquency according to socioeconomic status among Finnish adolescents from 2000 to 2015

Abstract: Background: Scientific literature suggests that the prevalence of delinquency amongst adolescents has decreased internationally in past decades. However, whether this change is consistent across all socioeconomic groups has not yet been studied. Objective: The aim of this study was to examine changes in delinquency amongst Finnish adolescents according to socioeconomic status between 2000 and 2015. Method: A population-based school survey was conducted biennially amongst 14-16-year-old Finns between 2000 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Torikka et al ( 2017 , 2014 ) observed increased socioeconomic differences in depression and alcohol consumption among Finnish adolescents between 2000 and 2011. Similarly, Knaappila et al ( 2018 , 2019b ) observed that the prevalences of delinquency and bullying at school increased among adolescents with low socioeconomic status only. In Finland, the economic depression in the 1990s led to marked increases in unemployment (Rotko et al 2011 ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Torikka et al ( 2017 , 2014 ) observed increased socioeconomic differences in depression and alcohol consumption among Finnish adolescents between 2000 and 2011. Similarly, Knaappila et al ( 2018 , 2019b ) observed that the prevalences of delinquency and bullying at school increased among adolescents with low socioeconomic status only. In Finland, the economic depression in the 1990s led to marked increases in unemployment (Rotko et al 2011 ).…”
Section: Discussionmentioning
confidence: 87%
“…Increased disparities in smoking may therefore have enhanced disparities in cannabis use. Increased socioeconomic health disparities have also been observed in other areas of adolescent health in Finland and other countries (Knaappila et al 2018 ; Knaappila et al 2019b ; Matthiessen et al 2014 ; Moraeus et al 2014 ; Torikka et al 2014 ; Torikka et al 2017 ). Torikka et al ( 2017 , 2014 ) observed increased socioeconomic differences in depression and alcohol consumption among Finnish adolescents between 2000 and 2011.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Epidemiological studies have shown no increasing trend in adolescent severe depression from the 1990s to the present, either internationally or in Finland, although some studies have reported an increased prevalence of self-reported depressive symptoms [33][34][35]. Externalizing problems have decreased steadily both internationally and in Finland [36]. Thus, changes in the epidemiology of disorders obviously do not explain the changes in inpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…To keep track of mental health in the population and to monitor the effectiveness of interventions on mental health disorders, data on the time trends of these disorders are needed. According to time trend studies in the 2000s and 2010s, mental health problems among Finnish adolescents have not increased (15)(16)(17)(18)(19). Instead, the demand for mental health services, especially for the treatment of depression and anxiety disorders, has recently increased among adolescents.…”
Section: Introductionmentioning
confidence: 99%